Vishwa Programme In Karnataka - A Preliminary Observation 1992-93 - Planning Commission (Planning Commission, 1992)
With a view to providing continuous productive employment in the rural areas, the Government of Karnataka started a Programme known as Vishwa1. This was launched by the Prime Minister on October 2, 1991. the Programme envisages strong marketing support to the goods and services produced in the rural sector assuring quality of products; institutional support for training; procurement of raw material; and finance to ensure generation of sustainable income of at least Rs. 750 to Rs. 1000 per month per beneficiary and revival and strengthening of sick tiny2 industrial units already established.
Programme Evaluation Organisation Planning Commission (Government of India)